Waiting for the Rain - Gordon, Sheila; Nang Chan Yeema (United States of America Bantam Books, 1997)
Tengo and Frikkie are childhood friends. Tengo is a black "boy" on Oom Koo's farm on the South African veld, and Frikkie is the white farmer's nephew, who one day will inherit the land.
Keywords: Adult Fiction